Foraging habitat characterization of green sea turtles, Chelonia mydas, in the Cenderawasih Bay, Papua, Indonesia: Insights from satellite tag tracking and seagrass survey (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Tapilatu RF, Wona H, Mofu B, Kolibingso D, Alzair N, Erdmann M, Marunaya B. 2022. Foraging habitat characterization of green sea turtles, Chelonia mydas, in the Cenderawasih Bay, Papua, Indonesia: Insights from satellite tag tracking and seagrass survey. Biodiversitas 23: 2783-2789. The distribution area of green turtles is not yet known in Cenderawasih Bay. On 20 November 2020, two satellite transmitters were attached to two female green turtles (Chelonia mydas Linnaeus, 1758) on Kalilemon, Southwest Cenderawasih Bay, Papua Province, Indonesia. Kalilemon area and Mangga Island as part of Kwatisore waters are the major foraging areas for this species and are under threat of turtle opportunistic poachers. The results show that the two turtles (Mary and Nona) dispersed and used limited but consistent and different foraging grounds during the tracking period through the satellite tags between November 2020-April 2021 at Mangga Island and Kalilemon. The composition of seagrass at both stations consisted of the same five species belonging to the families Cymodoceae and Hydrocharitaceae, with relatively different qualitative abundances. Overall, the mean chlorophyll-a content during the study period from November 2020-April 2021 ranged from 0.25-0.55mg/m3 at both foraging grounds (Mangga Island and Kalilemon). The mean SST during the study period ranged from 30.61-31.77oC in both locations. Before the next tracking attempt, more data on seasonal foraging and nesting activities are required. The result of this research is vital to determine the foraging grounds for green turtles related to the seagrass species with its abundance and key environmental factors in the management and conservation of sea turtles in the Cenderawasih Bay area.
Keywords: Chlorophyll-a, foraging ground, green turtle, Kalilemon, Mangga, Satellite transmitter, SST